Optimizing routing in quantum key distribution networks using the artificial fish swarm algorithm - Szczepanik, Wojciech; Niemiec, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
Quantum key distribution offers another way, alongside public key cryptography, of establishing cryptographic keys. The usage of quantum mechanics provides a high level of security at the cost of key establishment efficiency. To help with that, we propose a new link cost function used for establishing best paths in order to minimize key consumption. We optimize its parameters using the artificial fish swarm algorithm. The findings demonstrate that this approach enhances the performance of the quantum key distribution network.
Keywords: cybersecurity; routing; evolutionary algorithms; quantum key distribution; artificial fish swarm algorithm